The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4314/eamj.v77i3.46613
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of single and multiple species of helminth infections among school children in Busia District, Kenya

Abstract: Objective: To describe the patterns of single and multiple helminth infection in school children from Busia District, Kenya. Design: A cross-sectional school survey using a randomly selected sample, forming part of an evaluation study of an ongoing deworming project. Setting: Budalangi and Funyula divisions of Busia District, Western Province, Kenya. Subjects: One thousand seven hundred and thirty eight school children aged 8-20 years randomly selected from those enrolled in standards 3-8 in 25 randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 13 publications
10
64
2
1
Order By: Relevance
“…Finally, an increasing number of studies of helminth epidemiology have shown that it is common for individuals to be infected with more than one species of helminth (21,(58)(59)(60)(61)(62)(63). There is also evidence suggesting synergism and antagonism in concurrent intestinal nematode and schistosome infections (62-64) as well as filarial nematode infection and soil-transmitted helminth infections (65).…”
Section: Epidemiology Of Helminth Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an increasing number of studies of helminth epidemiology have shown that it is common for individuals to be infected with more than one species of helminth (21,(58)(59)(60)(61)(62)(63). There is also evidence suggesting synergism and antagonism in concurrent intestinal nematode and schistosome infections (62-64) as well as filarial nematode infection and soil-transmitted helminth infections (65).…”
Section: Epidemiology Of Helminth Infectionsmentioning
confidence: 99%
“…There is also evidence suggesting synergism and antagonism in concurrent intestinal nematode and schistosome infections (62-64) as well as filarial nematode infection and soil-transmitted helminth infections (65). A number of epidemiological studies have indicated that individuals infected with multiple species of helminth often harbor heavier infections than individuals infected with a single helminth species (58)(59)(60)(61). An important consequence of simultaneous infection with the parasites that cause hookworm, schistosomiasis, and malaria is severe anemia (21,66).…”
Section: Epidemiology Of Helminth Infectionsmentioning
confidence: 99%
“…Co-infection was common. Hookworm was the most prevalent helminth, but infection with S. mansoni was above 50% in three schools close to Lake Victoria, and above 30% in three other schools (Brooker et al, 2000). More recently, a survey of school-aged children living in lakeside and island locations in the Ugandan district next to Busia found that 75% of children were infected with S. mansoni and 33.6% were co-infected with soil-transmitted helminths (Kabatereine et al, 2011).…”
Section: Is Deworming Effectively Delivered In Ugandan Schools?mentioning
confidence: 99%
“…Geohelminths usually co-infect the host. Recent global estimates indicate that approximately 3.5 billion people are infected with one or more of the most common of these nematode parasites (STHs) [3,5], which cause more marked morbidity and disability than death (Table 1). The morbidity caused by helminths includes malnutrition, iron deficiency anemia, malabsorption syndrome, intestinal obstruction, chronic dysentery, rectal prolapse, respiratory complications, and poor weight gain [8,9].…”
Section: Introductionmentioning
confidence: 99%